Review of scalar control strategy of induction motor: constant v/f method for speed control (Balkan Journal of Applied Mathematics and Informatics, 2022)
This paper presents the design, simulation, and analysis of the speed control of an induction motor powered by a voltage inverter with a pulse-width modulation method. The derived model addresses issues related to the regulation of the motor speed at various supply frequencies. The control strategy of voltage inverter is based on the scalar control with a constant V/f ratio which is important for automated control, controlled start-up, acceleration and stop, and constant flux operation of the motor.  The Powersim software is used for the purposes of deriving the simulation model in this paper. The analysis of the output results compares the different speeds of operation, below and above the nominal speed of the motor. They are also compared with the theoretical calculations required for the simulation model.
Keywords: Scalar control strategy, Speed control, Induction motor, constant V/f control method, Powersim